ANTESEDEN INTENSI BELANJA PENGGUNA APLIKASI/WEBSITE TOKO ONLINE DI YOGYAKARTA - Faizal Ardiyanto; Hermala Kusumadewi (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2018)
In recent years, consumers are facilitated with online shop applications and websites. They are no longer needed to visit the “brick-and-mortar” shop to satisfy their needs and wants. Consumers can access the online shop as long as they smart phones are connected to internet network. Online shop also offers a great variety of products and services. This is an interesting topics to be discussed and researched. This reasearch is aimed to provide the evidence that there are positive affects among perceived security, ease of payment, trust in application/website, and online shopping intention. 450 respondents are participated in this research. Path analysis is used to examine the six hypotheses. The result shows that most of hypotheses are supported except H1b which states that perceived security positively affects online shopping intention. Keywords: online shop, smart phone, websites, perceived security, ease of payment, trust in application/website, online shopping intention, online consumers.